Body Mass Index Influences on Exertional Heat Stroke Risk in Young Healthy Males and Females - Farhan Fateh Jang, Muhammad Asif Khaskheli, Amna Malik, Tayyaba Rasheed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find the influence of body mass index on exertional heat stroke risk in young healthy males and females. Study Design: Retrospective case control study Place and Duration of Study: Department of Neurology, Sharif Medical & Dental College, Lahore from 1st April 2022 to 30th September 2022. Methodology: Two hundred patients who came with exertional heat stroke and compared it with the normal healthy control’s information were enrolled. Exertional heat stroke (EHS) cases were placed in Group A while normal controls in group B. The information regarding heat illness, body size, gender, was documented in addition to their other demographic details was compared in the groups. Results: The mean age of the EHS cases in group A was 25.5±7.2 years while of controls in group B was 26.1±6.5 years. There was higher number of males within both groups. The BMI of group A was higher than group B having a mean value as 26.9±3.2 in group A. The odds ration showed that EHS cases with a higher BMI had an increased risk of heat stroke which has a significant association with age but not with the gender. Conclusion: There is a significant association between the higher body mass index and exertional heat stroke formation in young adults. Keywords: Body weight, Outcome, Military, Influence, Marker